2023
DOI: 10.3390/su15021479
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Double-Diffusive Convection on Calculation Time and Accuracy Results of a Salt Gradient Solar Pond: Numerical Investigation and Experimental Validation

Abstract: The main aim of this study is to investigate numerically and experimentally the effects of double-diffusive convection on calculation time and accuracy results of a Salt Gradient Solar Pond (SGSP). To this end, two-numerical models are developed based on the Fortran programming language. The first one is based on energy balance neglecting the development of double-diffusive convection, while the second is two-dimensional and is based on Navier-Stokes, heat, and mass transfer equations considering the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The stability of the pond was experimentally studied to find dynamic methods of enhancing heat transport [77]. Experimental findings on the effect of double-diffusive convection on the calculation time were compared to numerical analysis with the numerical model giving more accurate thermal behaviors and a small error percentage [78]. The transient property of SGSP in the Mediterranean region has been investigated to prove that thermal energy is stored as sensible heat [79].…”
Section: Salt Gradient Solar Pond (Sgsp)mentioning
confidence: 99%
“…The stability of the pond was experimentally studied to find dynamic methods of enhancing heat transport [77]. Experimental findings on the effect of double-diffusive convection on the calculation time were compared to numerical analysis with the numerical model giving more accurate thermal behaviors and a small error percentage [78]. The transient property of SGSP in the Mediterranean region has been investigated to prove that thermal energy is stored as sensible heat [79].…”
Section: Salt Gradient Solar Pond (Sgsp)mentioning
confidence: 99%
“…The salt-gradient solar pond (SGSP) is one of these systems. Rghif et al conducted extensive in-depth research to further improve the performance and efficiency of SGSP systems [2][3][4][5]. STS can effectively solve the mismatch between the supply of and demand for thermal energy in time and space, and the solar fraction and operational stability of solar-heating systems can be significantly improved.…”
Section: Introductionmentioning
confidence: 99%
“…4,12,35,36 Similarly, scientists have also studied the factors contributing to the decrease in efficiency of salt gradient solar ponds. [37][38][39][40][41][42][43][44] Wang et al 23 experimented to investigate the impact of varying porosity levels (61%, 65.5%, 67%, and 74%) of a porous material on salt diffusion within Salt Gradient Solar Ponds (SGSPs). The results indicated that the porous material could delay salt diffusion from the Lower Convective Zone (LCZ) to the Upper Convective Zone (UCZ), with lower porosity leading to slower diffusion.…”
Section: Introductionmentioning
confidence: 99%